On countable almost invariant partitions of g-spaces - Kharazishvili, A.B. (Український математичний журнал, 2014)
For any σ -finite G-quasiinvariant measure μ given in a G-space, which is G-ergodic and possesses the Steinhaus property, it is shown that every nontrivial countable μ-almost G-invariant partition of the G-space has a μ-nonmeasurable member. Для будь-ям'ї σ -скінченної G-квазіінваріантної міри μ, що задана на G-прсторні, є G-ергодичною та має властивість Штейнхауса, показано, що кожне нетривіальне розбиття μ-майже G-інваріантного розбиття G-простору має μ-невимірний член.